The Impact of COVID-19 Pandemic on Students’ Learning Behavior.: The Case of Master 1 EFL Students- University of Saida - ALGERIA - SAHNOUNE, Nesrine; Ghembaza, Ahmed Hichem (LANGUAGE ART, 2023)
The current study investigates the impact of COVID-19 epidemic on the learning behavior of Master1 EFL students –University of Saida - Algeria. To fulfill the study’s objectives, a mixed method approach encompassing both quantitative and qualitative methods was used to compile, analyze and interpret data. Two research tools, a questionnaire and an interview were delivered to the students and teachers respectively at the Department of English – University of Saida - Algeria. In the light of the obtained results, students were reported to hold negative attitudes towards COVID-19 pandemic, resulting in a lot of psychological problems such as anxiety, depression, and lack of motivation. From a cognitive perspective, the study revealed that the negative impact of the pandemic is related to students’ cognitive learning styles such as the challenges that EFL field-dependent learners face when studying online .Conversely, COVID-19 outbreak had a positive cognitive influence on field-independent learners in relation to online learning.